Using Kahoot! To Create a Fun English Vocabulary During Learning Process - Alawiyah, Rosidah; Wahyuni, Ika Yuli; Muhid, Abdul (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aimed to improve students’ vocabulary learning using Kahoot! The study used a descriptive quantitave research. The subjects were taken from VIII H at a state SMP in Makassar. There were two data collection instruments used in this research, vocabulary test and questionnaire. The result showed that the learning vocabulary using kahoot process can be improved. The pre-test showed that students’ average score was (58.10) and the post- test score average was (81.33). It concluded that using kahoot can improve English vocabulary achievement